Endothelial dysfunction and its correction with perindopril therapy in patients with coronary heart disease - O. A. Vartanova (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To investigate endothelial dysfunction (ED) in patients with coronary heart disease (CHD), stable effort angina, Functional Class (FC) I-III, as well as to study perindopril potential in ED correction.Material and methods. The study included 37 CHD patients (22 men, 15 women; mean age 62,2+5,3 years) with FC I-II (n=22) and FC III angina (n=15). The control group included 16 healthy individuals. Fndothelium-dependent vasodilatation (FDVD) of brachial artery (BA) was assessed in reactive hyperemia test at baseline and after 6 weeks of perindopril therapy (8 mg/d); in controls, FDVD was assessed at baseline only.Results. At baseline, ED was observed in 79 % of CHD patients: in 42 %, as an inadequate vasodilatation effect (< 10 % from the baseline), and in other 37 %, as no BA diameter increase or vasoconstriction. ED was more prevalent in individuals with FC III angina (93 %) than in participants with FC I-II angina (69 %). Perindopril therapy was associated with increased numbers of patients with vasodilatation > 10 % (+9 %)or<10 % (+3,5 %), while the number of participants with vasoconstriction reduced by 12,5 %. The number of ED participants reduced by 26 % and 8 % for FC I-II and FC III, respectively. Among those with FC I-II angina, perindopril treatment was associated with significant increase in BA diameter (+9,8 %; p<0,05), linear and volumic blood flow velocity (from 15,0+1,9 to 41,5+2,1 cm/s (p<0,05) and from 2,1+0,5 to 6,9+0,5 ml/s (p<0,05), respectively).Conclusion. Adding perindopril (8 mg/d) to standard anti-ischemic therapy was associated with reduced ED, which could be regarded as a vasoprotective perindopril effect.